(untitled) (Филолошки студии, 2019)
In this paper has reserved area for history of the plague and cholera in Macedonia in 18 and 19th century. The epidemics a little known but substantial factor for the on-going changes in cultural and spiritual attitudes and practices in Ottoman Empire in this period. That fearful epidemics occurred periodically throughout those years and destructive effect upon the lives of people in Macedonian villages and towns. Those were disrupted the normal economic rhythm and caused many people to flee from their homes and thus leading as well to serious changes in the system of existing settlements. The changes underway second half 19 th century had opened new horizons to and methods for preventing and handling with the epidemics.